2014
DOI: 10.1371/journal.pone.0108935
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotopes in Fish Eye Lenses as Potential Recorders of Trophic and Geographic History

Abstract: We evaluated eye lenses as potential recorders of stable isotope histories in fish because they consist of metabolically inert optical proteins that are deposited in successive, concentric circles (laminae) much like otolith circuli and tree rings. We conducted four different tests on lenses from red snapper, red grouper, gag, and white grunt. The first test was a low-resolution screening of multiple individuals (4–5 radial groups of laminae per lens, all species except white grunt). Along the radial axis, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 37 publications
2
63
0
Order By: Relevance
“…While some findings suggest that scale Sr : Ca correlates with concentrations in ambient water and otoliths (Wells et al 2003a;Campbell et al 2015), others have found no such relationship (Clarke et al 2007). Complicating the matter, Weakfish (Cynoscion regalis) scale and otolith Sr : Ca were found to be dissimilar in 1-yr-old fish but comparable at age two, possibly due to elemental remobilization in older individuals (Wells et al 2003b). Courtemanche et al (2006) noted that even the subset of scales chosen for analysis affected the detection of a Sr : Ca correlation between otoliths and scales, and suggested scales may become an unreliable indicator of Sr once diadromous fish encounter the marine environment.…”
Section: Tzadik Et Almentioning
confidence: 97%
See 2 more Smart Citations
“…While some findings suggest that scale Sr : Ca correlates with concentrations in ambient water and otoliths (Wells et al 2003a;Campbell et al 2015), others have found no such relationship (Clarke et al 2007). Complicating the matter, Weakfish (Cynoscion regalis) scale and otolith Sr : Ca were found to be dissimilar in 1-yr-old fish but comparable at age two, possibly due to elemental remobilization in older individuals (Wells et al 2003b). Courtemanche et al (2006) noted that even the subset of scales chosen for analysis affected the detection of a Sr : Ca correlation between otoliths and scales, and suggested scales may become an unreliable indicator of Sr once diadromous fish encounter the marine environment.…”
Section: Tzadik Et Almentioning
confidence: 97%
“…Other exploratory work has been conducted on squid lenses; squid have a complex eye much like vertebrates (Parry 2003;Hunsicker et al 2010). Wallace et al (2014) also called for further experimentation with respect to aging eye lenses as well as conducting compound specific isotope analyses.…”
Section: Stable Isotope Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Another alternative, albeit relatively unexplored, tissue type which can be used to estimate longevity, and reconstruct lifetime patterns of movement and migration of fishes is the eye lens (Nielsen et al., ; Quaeck‐Davies et al., ; Wallace, Hollander, & Peebles, ). The eye lens is useful for species which do not possess hard structures such as otoliths (e.g., elasmobranchs), or in cases where vertebral sampling cannot be conducted (e.g., endangered species or tagged fish).…”
Section: Contemporary Movement Studies and The Development Of Novel Mmentioning
confidence: 99%
“…The eye lens is useful for species which do not possess hard structures such as otoliths (e.g., elasmobranchs), or in cases where vertebral sampling cannot be conducted (e.g., endangered species or tagged fish). Fish eye lenses are metabolically inert and incrementally grown in concentric layers called laminae (Dahm, Schonthaler, Soehn, Van Marle, & Vrensen, ; Wallace et al., ). The oldest cells reside within the central core, whereas the newest layers are deposited at the lens margin (Quaeck‐Davies et al., ; Wallace et al., ).…”
Section: Contemporary Movement Studies and The Development Of Novel Mmentioning
confidence: 99%